Protein Turnover in Escherichia coli as Measured with an Equilibration Apparatus - Levine, Elliot M. (1965)
Levine, Elliot M. (National Institutes of Health, Bethesda, Md.). Protein turnover in Escherichia coli as measured with an equilibration apparatus. J. Bacteriol. 90:1578–1588. 1965.—Intercellular protein turnover (the reutilization by one cell of amino acids derived from the protein of another cell) occurs at a rate of 0.16 to 0.18% per hour in nongrowing cultures of Escherichia coli, as determined in an apparatus that rapidly equilibrates the culture fluids of two separated bacterial suspensions.